1995
DOI: 10.1088/0953-4075/28/10/004
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative ionization of molecules in intense laser fields: a method of predicting ion kinetic energies and appearance intensities

Abstract: We pment a model lo describe certain aspens of the multiphoton multielectron dissociative ionization of simple molecules m tnteme laser fields. We obtain fragment ion dissociation energies and appearance Intensities that are in good agreement with experiment.The multielectron dissociative ionization of diatomic and triatomic molecules in intense laser fields (focal intensities W cm-*) is not understood. Recent experiments indicate that all fragment ions emerge with dissociation energies which are specific fiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 11 publications
5
113
0
1
Order By: Relevance
“…It was inferred that CE occurs at a larger critical bond length R C due to bond softening induced by the laser field [10,15,16]. Various models have been developed to explain this reduction in Coulomb energy, for example, the two-step model [10], the Thomas-Fermi-Dirac (TFD) model [17], the charge transfer enhanced ionization (CREI) model [15,16,[18][19][20][21] and the Molecular Ammosov-Delone-Krainov (MO-ADK) model [22][23][24]. The temporal rise of the E-field amplitude laser pulse brings about a weakening of the binding energy of the valence electrons to the molecules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was inferred that CE occurs at a larger critical bond length R C due to bond softening induced by the laser field [10,15,16]. Various models have been developed to explain this reduction in Coulomb energy, for example, the two-step model [10], the Thomas-Fermi-Dirac (TFD) model [17], the charge transfer enhanced ionization (CREI) model [15,16,[18][19][20][21] and the Molecular Ammosov-Delone-Krainov (MO-ADK) model [22][23][24]. The temporal rise of the E-field amplitude laser pulse brings about a weakening of the binding energy of the valence electrons to the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the molecule ionizes predominantly at R ≈ R C . The fragment ions born out of such a CE usually give rise to an anisotropic angular distribution which favors the direction of the polarization vector of the laser field [18,[25][26][27][28][29][30][31][32][33][34]. Such anisotropic angular distributions are characteristic for a CE based on a dynamic or a geometric alignment mechanism or on a combination of these two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that even in the heavy I 2 molecule a dynamic alignment must take place, or at least the laser must impart a substantial impulse to the fragments [4,5]. However, these ideas were formulated prior to the discovery of enhanced ionization at the critical internuclear separation [6][7][8]. As the molecule dissociates with about twice the equilibrium separation, the ionization threshold drops by about an order of magnitude if the molecule is parallel to the field but stays almost constant if the molecule is in an orthogonal orientation.…”
mentioning
confidence: 99%
“…The double ionization of molecular hydrogen through enhanced ionization is well documented in the literature and heavily studied theoretically [11][12][13][14]. In recent years two additional double ionization processes have been identified and modelled: rescattering ionization [15][16][17][18][19][20][21] and sequential ionization [22,23].…”
Section: Sequencing Emission Of Ion Pairs In Molecular Hydrogenmentioning
confidence: 99%